Vocal activity of the Ferruginous pygmy-owl (Glaucidium brasilianum) is strongly correlated with moon phase and nocturnal temperature. Issue 1 (2nd January 2021) - Pérez-Granados, Cristian; Schuchmann, Karl-L.; Marques, Marinez I.
Abstract : Bird vocal activity is affected by endogenous and exogenous factors. Owl surveys are mainly based on the detection of nocturnal calls, and therefore, the impact of exogenous factors on owls' vocal activity may have consequences in conservation planning and behavioural studies. However, our current knowledge about the impact of climatic factors and the moon phase on owl calling behaviour is very limited, especially in the Neotropics. We used autonomous recording units to evaluate the effect of air temperature, rainfall, relative air humidity, and percent of the moon illuminated on the vocal occurrence (active/inactive) of the Ferruginous pygmy-owl ( Glaucidium brasilianum ) over three consecutive moon cycles in the Brazilian Pantanal. Vocal activity was positively associated with the percent of the moon illuminated, with 75% of the nights on which the species was vocally active having a moon illumination percentage higher than 77%. The vocal activity of the species was negatively associated with the nocturnal air temperature, with more vocal activity observed on cooler nights. Relative air humidity and daily rainfall were not associated with the vocal activity of the Ferruginous pygmy-owl. Our study improves the knowledge about the impact of exogenous factors on the calling behaviour of Neotropical owls. We conclude that future surveys aiming to detect the Ferruginous pygmy-owl should be carried out on nights with a high percent of moon illumination (>75%) and nights with low average temperature (< 18 °C).